REACH MUSC: A Telemedicine Facilitated Network for Stroke: Initial Operational Experience - Adams, Robert J.; Debenham, Ellen; Chalela, Julio; Chimowitz, Marc; Hays, Angela; Hill, Cody; Holmstedt, Christine; Jauch, Edward C.; Kitch, Alec; Lazaridis, Christos; Turan, Tanya N. (Frontiers in Neurology, 2012)
REACH MUSC provides stroke consults via the internet in South Carolina. From May 2008 to April 2011 231 patients were treated with intravenous (IV) thrombolysis and 369 were transferred to Medical University of South Carolina (MUSC) including 42 for intra-arterial revascularization (with or without IV tPA). Medical outcomes and hemorrhage rates, reported elsewhere, were good (Lazaridis et al. 2011, in press). Here we report operational features of REACH MUSC which covers 15 sites with 2,482 beds and 471,875 Emergency Department (ED) visits per year. Eight Academic Faculty from MUSC worked with 165 different physicians and 325 different nurses in the conduct of 1085 consults. For the 231 who received tissue plasminogen activator (tPA), time milestones were: Onset to Door: 62 min (mean), 50 (median); Door to REACH Consult: 43 and 33, Consult Request to Consult Start: was 9 and 7 minutes, Consult Start to tPA Decision: 31 and 25 minutes; Decision to Infusion: 20 and 14 minutes, and total Door to Needle: 98 and 87 minutes. The comparable times for the 854 not receiving tPA were: Onset to Door: 140 and 75 minutes; Door to REACH Consult: 61 and 41 minutes; Consult Request to Consult Start 9 and 7 minutes, Consult Start to tPA Decision 27 and 23 minutes. While the consultants respond to consult requests in < 10 minutes, there is a long delay between arrival and Consult request. Tracking of operations indicates if we target shortening Door to Call time and time from tPA decision to start of drug infusion we may be able to improve Door to Needle times to target of < 60 minutes. The large number of individuals involved in the care of these patients, most of whom had no training in REACH usage,will require novel approaches to staff education in ED based operations where turnover is high. Despite these challenges this robust system delivered tPA safely and in a high fraction of patients evaluated using the REACH MUSC system.